EVALUASI PEMELIHARAAN RUNWAY DI BANDAR UDARA HUSEIN SASTRANEGARA BANDUNG - Rian Riandi; Nidya Novalia; Albert Kurniawan Purnomo (Jurnal Deformasi, 2022)
The facilities available at the airport affect the smooth operation of airline operations at an airport. One of the factors causing flight delays is operational technical factors which include the condition of airport facilities (runway) or runways that cannot be used, this study uses qualitative research methods because using this method is more of a clear description of a problem in accordance with the facts in the field. Based on the results of research at Husein Sastranegara Airport, runway maintenance is very influential on operational activities of aviation security and safety, therefore maintenance and repair activities are very important..